Analisis Psikologi Sastra dalam Cerpen Siber “Lagu Malam yang Terpenggal” Karya Indra Tranggono - Tasya Rianti; Neng Rini Sugihartini; Syifa Halimatussadiyah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The cyber short story “Lagu Malam yang Terpenggal” by Indra Tranggono presents a narrative full of psychological struggles of its characters. This study aims to identify and analyze the psychological elements experienced by the main characters, Ibu and Sawitri, and how the narrative structure of the short story supports the depiction of these psychological conditions. The research method used is descriptive qualitative with a literary psychology approach. The results of the analysis show that the Ibu character experiences deep trauma due to the loss of her child, which is manifested in repetitive behavior and false beliefs and indications of hallucinations. Meanwhile, Sawitri struggles with internal conflict, guilt and psychosocial stress. The climax of the story presents an emotional confrontation that reveals deep psychological wounds and triggers traumatic anger. This short story effectively depicts the psychological impact of loss and uncertainty through characterization and dialogue. This study concludes that the short story “Lagu Malam yang Terpenggal” successfully explores the complexity of emotions and trauma through a psychological approach highlighting the inability of individuals to accept the bitter reality and psychological burden due to the injustice of the social system.